2006
DOI: 10.1097/01.mnm.0000243371.26507.3c
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cancer cell proliferation, tumour angiogenesis and 201Tl uptake in non-small cell lung cancer

Abstract: 201Tl SPECT imaging is effective non-invasive method for assessing both the proliferation and the angiogenesis in NSCLC. Both DR and RI are useful indicators for assessing cancer cell proliferation in lung adenocarcinoma. ER is a useful marker for assessing the tumour angiogenesis in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Earlier, we reported the close association between the early uptake of 201 Tl and tumor angiogenesis [8,9]. We also found that the positive correlation between delayed uptake of 201 Tl and cancer cell proliferation or lymph node metastasis potential [8,9]. However, the infl uence of blood fl ow may remain on the conventional delayed image in NSCLC patients such as the cases with complicated infl ammation.…”
Section: Introductionmentioning
confidence: 50%
See 3 more Smart Citations
“…Earlier, we reported the close association between the early uptake of 201 Tl and tumor angiogenesis [8,9]. We also found that the positive correlation between delayed uptake of 201 Tl and cancer cell proliferation or lymph node metastasis potential [8,9]. However, the infl uence of blood fl ow may remain on the conventional delayed image in NSCLC patients such as the cases with complicated infl ammation.…”
Section: Introductionmentioning
confidence: 50%
“…It is known that retention index of 201 Tl is closely related with cellular malignancy such as differentiation degree or proliferation potential [8,9,12,14]. Earlier, we also reported the close connection between tumor 201 Tl uptake and angiogenesis or cell proliferation [9]. We reevaluated the issue using a super-delayed image in the current study.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…MVD and EA have been experimentally proposed to be biomarkers associated with biological aggressiveness and clinical outcome in animal and human malignancies. In regards to pancreatic cancer, it has been established that angiogenesis has a role in its development and progression (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). In addition, Ki-67 expression is an important parameter for biological aggressiveness and prognosis in tumour tissue; Ki-67 antigens are initially expressed in S-phase and increase throughout S-and G 2 -phase until they reach their peak expression during mitosis.…”
Section: Introductionmentioning
confidence: 99%